Functional nanoporous materials from boronate-containing stimuli-responsive diblock copolymers. Issue 20 (20th April 2022) - Bakangura, Erigene; Fournier, David; Coumes, Fanny; Woisel, Patrice; Grande, Daniel; Le Droumaguet, Benjamin
Abstract : Functional nanoporous polymeric materials have been prepared from novel polystyrene- block -poly(ethylene oxide) (PS- b -PEO) diblock copolymer precursors containing a reversible boronate ester junction between both blocks. Abstract : Functional nanoporous polymeric materials have been prepared from novel polystyrene- block -poly(ethylene oxide) (PS- b -PEO) diblock copolymer precursors containing a reversible boronate ester junction between both blocks. To this purpose, homopolymers presenting either a boronic acid or a (nitro)catechol end functionality were synthesized. The coupling of each homopolymer presenting complementary chemical functions was successfully achieved under mild conditions and allowed for the generation of the corresponding boronate ester-containing diblock copolymers. Upon orientation of these precursors on silicon wafers via solvent vapor annealing, the resulting films were submitted to PEO etching through selective cleavage of the boronate ester junction under mild acidic conditions. SEM micrographs of the as-obtained thin films revealed the generation of 12 nm-diameter oriented cylindrical nanopores perpendicular to the silicon support surface.